Media Pembelajaran Perspektif Al-Qur’an Surah Al-Baqarah Ayat 31 - Izzan, Ahmad; Nuraeni, Neni (STAI Al-Musaddadiyah Garut, 2023)
Educational media is one of the crucial aspects that educators must master. It significantly impacts the success of the teaching and learning process. By using a variety of educational media, educators can foster and develop students' interest and talents in learning. This approach can simplify the comprehension of material, keeping students engaged and preventing boredom, thus promoting direct interaction between educators and students. The Qur'an contains numerous verses discussing educational media, notably in Surah Al-Baqarah, Verse 31. This verse encompasses several values related to educational media. This research aims to describe the educational media concepts embedded in Surah Al-Baqarah, Verse 31 of the Qur'an. It employs a library research method through an analytical approach and includes a comparative study to examine the factors and consequences based on documents and literature. The research is inductive, aiming to generate theories through the exploration of facts by analyzing the interpretations of scholars regarding Surah Al-Baqarah, Verse 31, and reviewing written sources about educational media proposed by experts and Islamic scholars. The qualitative research method focuses on content analysis of the Qur'anic verse and relevant texts. The findings reveal that the value associated with educational media in Surah Al-Baqarah, Verse 31, pertains to